THE INFLUENCE OF ELECTRONIC WORD OF MOUTH AND BRAND IMAGE ON CONSUMER PURCHASE DECISIONS FOR COSMETICS WARDAH AT AMELIA OLSHOP IN DISTRICT CIPONDOH CITY TANGERANG - Akrimah, Nadia; Salami, Muhammad Musyfiq (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to investigate The Influence of Electronic Word of Mouth and Brand Image on Consumer Purchase Decisions of Wardah Cosmetics at Amelia Olshop in Cipondoh District, Tangerang City, both partially and simultaneously. The type of research method used is associative with a quantitative approach. The population for this study consists of Wardah cosmetics buyers at Amelia Olshop. The sample was determined using Slovin's formula, resulting in 98 respondents. Data collection was conducted through questionnaires, and data analysis techniques included validity tests, reliability tests, classical assumption tests, linear regression tests, correlation coefficient tests, coefficient of determination tests, partial t-tests, and simultaneous F-tests, utilizing SPSS Version 26. The results showed that Electronic Word of Mouth (X1) had a t-value of 2.546 > t-table value of 1.660 with a significance value of 0.012 < 0.05; therefore, H1 is accepted. This concludes that Electronic Word of Mouth has a significant positive effect on purchasing decisions (accepted). Brand image (X2) had a t-value of 7.267 > t-table value of 1.660 with a significance value of 0.000 < 0.05; thus, H2 is accepted. This concludes that Brand image also has a significant positive effect on purchasing decisions (accepted). The F-test result shows that the calculated F-value of 48.481 > F-table value of 4.74, with a significance probability of 0.000 < 0.05, which means H1 is accepted. It can be stated that both Electronic Word of Mouth and Brand image simultaneously influence purchasing decisions.